2012
DOI: 10.1038/srep00509
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoprotein filament formation is the structural basis for bacterial protein H-NS gene silencing

Abstract: H-NS is an abundant nucleoid-associated protein in bacteria that globally silences genes, including horizontally-acquired genes related to pathogenesis. Although it has been shown that H-NS has multiple modes of DNA-binding, which mode is employed in gene silencing is still unclear. Here, we report that in H-NS mutants that are unable to silence genes, are unable to form a rigid H-NS nucleoprotein filament. These results indicate that the H-NS nucleoprotein filament is crucial for its gene silencing function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 35 publications
7
101
1
Order By: Relevance
“…DNase footprinting on the clpV promoter further showed that H-NS binds to different regions, including the Ϫ35 box, and then spreads on downstream and upstream fragments. This observation is consistent with the two-step mechanism of H-NS silencing in which H-NS first binds to high-affinity sites that nucleate cooperative binding, leading to H-NS polymerization onto adjacent DNA regions (54,55,65,73). H-NSdependent silencing of the S. Typhimurium T6SS gene cluster is not an isolated case as previous studies showed that the Acinetobacter baumannii, Pseudomonas aeruginosa HSI-2 and HSI-3, Pseudomonas Putida, and Vibrio parahaemolyticus T6SS gene clusters as well as the Edwardsiella tarda T6SS evpP-evpO genes are repressed by H-NS-like proteins (80)(81)(82)(83)(84).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…DNase footprinting on the clpV promoter further showed that H-NS binds to different regions, including the Ϫ35 box, and then spreads on downstream and upstream fragments. This observation is consistent with the two-step mechanism of H-NS silencing in which H-NS first binds to high-affinity sites that nucleate cooperative binding, leading to H-NS polymerization onto adjacent DNA regions (54,55,65,73). H-NSdependent silencing of the S. Typhimurium T6SS gene cluster is not an isolated case as previous studies showed that the Acinetobacter baumannii, Pseudomonas aeruginosa HSI-2 and HSI-3, Pseudomonas Putida, and Vibrio parahaemolyticus T6SS gene clusters as well as the Edwardsiella tarda T6SS evpP-evpO genes are repressed by H-NS-like proteins (80)(81)(82)(83)(84).…”
Section: Discussionsupporting
confidence: 73%
“…This observation suggests that H-NS spreads from an initial, high-affinity binding site used as a nucleation center to occupy an extensive DNA region. These characteristics of H-NS have already been studied in detail in previous work and have been proposed to be responsible for gene silencing (54,65,73).…”
Section: Resultsmentioning
confidence: 96%
“…This region has a very high AT content (69.3%) with respect to that of the entire S. Typhimurium genome (47.8%), consistent with the fact that H-NS binds to and acts on AT-rich sequences (42,43). H-NS represses gene expression by forming nucleoprotein complexes, which trap or exclude the RNA polymerase at or from promoters, mainly by two mechanisms (45,46,(54)(55)(56)(57). By the first mechanism, H-NS binds to two sites located further apart, upstream and downstream of the promoter, and then induces a DNA-H-NS-DNA bridge that forms a repressor nucleoprotein stem-loop.…”
Section: Discussionmentioning
confidence: 82%
“…H-NS is a small (ϳ136-aminoacid) protein that preferentially binds as a dimer to curved double-stranded DNA, although it can also induce bending of noncurved DNA upon binding. H-NS is thought to repress gene expression by oligomerizing along the DNA from its primary nucleation sites or by bridging adjacent DNA segments, thus blocking RNA polymerase access to promoter sequences or preventing the formation of an active open complex (41,42). It has also been demonstrated that H-NS silences genes that are thought to have been acquired by horizontal transfer events, thus preventing the fitness cost for the receptor cell while newly acquired genes (including virulence factors) are integrated into and controlled by preexisting regulatory networks (reviewed in references 43 and 44).…”
Section: Discussionmentioning
confidence: 99%